269 ORAL ADMINISTRATION OF METALLOPORPHYRINS AND ITS SYSTEMIC EFFECTS ON HEME OXYGENASE EXPRESSION. (1st January 2005) - Morioka, I.; Wong, R. J.; Abate, A.; Vreman, H. J.; Contag, C. H.; Stevenson, D. K.
Abstract : Metalloporphyrins (Mps) inhibit heme oxygenase (HO), the rate-limiting enzyme in the production of bilirubin, and are potential compounds for use in the chemoprevention of neonatal jaundice. . Our object was to monitor the effects of selected Mps on in vivo heme degradation and HO-1 gene transcription, and in vitro HO enzyme activity and protein levels after oral administration. 30 μM of tin mesoporphyrin (SnMP), zinc bis glycol porphyrin (ZnBG), zinc protoporphyrin (ZnPP), or vehicle was orally administered to adult HO-1-luc transgenic mice. In vivo heme degradation rates were measured as total body CO excretion levels (VeCO) by GC. In vivo HO-1 transcription levels were assessed by bioluminescence imaging (BLI). In vitro HO activity was quantitated via CO measurements by GC. HO-1 protein levels were determined by Western blot. VeCO decreased 28% within 3 h of SnMP treatment and lasted beyond 48 h. Administration of ZnBG and ZnPP decreased VeCO 15% and 9%, respectively, by 3 h. HO-1 transcription increased only in SnMP-treated mice (6.5-fold) after 24 h. % inhibition of tissue HO activities are shown below: (Table ) HO activity was maximally inhibited in liver, spleen and intestine within 3 h, with the greatest inhibition in SnMP mice, then in ZnBG, with the least in ZnPP mice. Furthermore, in SnMP mice, liver and spleen HO-1 protein levels significantly increased 3.5- and 2.0-fold, respectively, after 24 h. HO-1 protein was minimally affected in ZnBG- or ZnPP-mice. These results are in contrast to our previous findings in neonatal rat pups, where ZnPP was not orally absorbable. Therefore, we conclude that orally administered Mps are absorbed variably and affect HO expression in a species- as well as in a tissue- and time-dependent manner.